2009
DOI: 10.1007/s10522-009-9225-3
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide adenine dinucleotide extends the lifespan of Caenorhabditis elegans mediated by sir-2.1 and daf-16

Abstract: It is well understood that sir2 (sirtuin), an NAD-dependent deacetylase, is essential for the extension of lifespan under caloric restriction. However, the mechanism underlying activation of sir2 is unclear. Life extension through caloric restriction requires the sir2 ortholog sir-2.1 in nematodes but occurs independently of the forkhead-type transcription factor DAF-16. We aimed here to elucidate the correlation between life extension in nematodes and NAD-dependent activation of sirtuin by analyzing the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…SIR proteins (collectively known as sirtuins) belong to a conserved family of nicotinamide adenine dinucleotide (NAD)-dependent deacetylases (class III NAD+-dependent deacetylase) implicated in the regulation of life span under calorie restriction. Their key role is in regulating glucose and lipid metabolism [135][136][137][138] . In mammals, there are seven homologs of SIR (SIRT1-7).…”
Section: Sirtuins Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIR proteins (collectively known as sirtuins) belong to a conserved family of nicotinamide adenine dinucleotide (NAD)-dependent deacetylases (class III NAD+-dependent deacetylase) implicated in the regulation of life span under calorie restriction. Their key role is in regulating glucose and lipid metabolism [135][136][137][138] . In mammals, there are seven homologs of SIR (SIRT1-7).…”
Section: Sirtuins Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…The differential distribution of sirtuins implicates their distinct roles in cytosolic, mitochondrial, and nuclear events. SIRT1 is predominantly localized to the nuclear compartment and is implicated in regulating the transcriptional and epigenetic regulation of gene expression [135][136][137][138] . In contrast, SIRT2 is cytosolic, and SIRT3, SIRT4, and SIRT5 are mainly mitochondrial sirtuins [135][136][137][138] .…”
Section: Sirtuins Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Importantly, overexpression of Sir2, a histone deacetylase required for heterochromatin formation and gene silencing, induces an increased lifespan in yeast (Kaeberlein et al ., 1999). The connection between heterochromatin maintenance and lifespan extension is further strengthened by studies in Caenorhabditis elegans and Drosophila (Rogina & Helfand, 2004; Hashimoto et al ., 2010; Jiang et al ., 2013; Whitaker et al ., 2013). Disruption of UTX‐1, a histone demethylase that reduces the heterochromatin epigenetic modification called histone H3 K27 trimethylation (H3K27me3), in C. elegans leads to increased H3K27me3 levels and prolonged lifespan (Jin et al ., 2011; Maures et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, accumulated data also show that the life-extending effects of CR are attributable to the increase of concentration of NAD ? , which then activates sirtuins (Lu and Lin 2010;Hashimoto et al 2010;Wood et al 2004). Our findings that 2-DG can extend lifespan of Hs68 cells in parallel with increased intracellular NAD ?…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that life extension of CR in organisms is mediated through the activation of Sirtuins (e.g., Sir2 in yeast and SIRT1 in human), possibly via sensing the increase of cellular NAD ? levels (Lu and Lin 2010;Kyrylenko and Baniahmad 2010;Hashimoto et al 2010;Ghosh 2008;Wood et al 2004). To date, it has become an interesting area for anti-aging research on CRM via the activation of sirtuins by pharmacological means (Ingram et al 2006;Chen and Guarente 2007;Aljada et al 2010).…”
Section: Introductionmentioning
confidence: 99%